The Interface Between Spirituality and Violence in the Lives of Immigrant African Women: Implications for Help Seeking and Service Provision. Issue 1 (2nd January 2016) - Ting, Laura; Panchanadeswaran, Subadra
ABSTRACT: Immigration is one of many risk factors for intimate partner violence (IPV) due to the resulting stressors of acculturation and discrimination, in addition to economic changes in the family. Research is limited on African immigrant survivors of IPV in the United States, specifically in terms of women's experiences with faith-based leaders when seeking help. Although informal help seeking with family elders is the preferred help-seeking method, in light of limited family support available in the United States, women often seek help from faith-based leaders. This qualitative study explored 15 African women's experiences and perceptions of help seeking with faith-based leaders, and examined the role of spirituality in the lives of African immigrant women who experience IPV. Results indicate experiences of feeling blamed, stigmatized, and misunderstood, in addition to lack of practical help. Women's self-isolation, however, did not preclude them from engaging in spiritual behaviors, forgiveness, and beliefs in God's benevolence and future justice. Implications for coordinated responses between secular service providers and faith-based leaders and future research are discussed.